Assessment of ibuprofen, non-selective cox inhibitor, as a neuroprotective agent in Alzheimer’s model of rats - Saxena, Anil Kumar; Mohd, Fadly; Talib, Norlelawati A. (2013)
Aging related reduction in cerebral blood flow (CBF) has been associated with neurodegenerative disorders including Alzheimer’s disease and dementia. Experimentally, a condition of chronic cerebral hypoperfusion due to reduced CBF can be induced by permanent bilateral occlusion of common carotid arteries (2-vessel occlusion, 2VO) in rats. Since neuroinflammation, leading to neuronal apoptosis and death, is one of the mechanisms which is thought to play a significant role in chronic degenerative neurological disorders, the present study was planned to assess the neuroprotective role of ibuprofen in chronic cerebral hypoperfusion-induced neurodegeneration. After acclimatization, fifteen Sprague Dawley rats weighing 200-250 g were equally divided into three groups. Group A – sham control, Group B – 2VO, and Group C – 2VO-I (treated daily with ibuprofen, 50 mg/kg, orally following 2VO). On 8th week, all the rats were euthanized and the hippocampi were isolated. Viable neuronal cell count in the hippocampal CA-1 region, hippocampal COX-2 mRNA expression and prostaglandin E2 (PGE-2) levels were estimated. There was a significant difference in neuronal cell death, increase in COX-2 mRNA expression and PGE-2 levels in 2VO group as compared to sham control group. In ibuprofen-treated 2VO (2VO-I) rats, the viable neuronal cell count of the hippocampal CA-1 region was significantly higher as compared to the untreated 2VO group. For the hippocampal COX-2 mRNA expression, the value in the ibuprofen treated group showed insignificant difference when compared to the untreated 2VO group. However, hippocampal PGE-2 levels were found to be significantly lower in the ibuprofen treated 2VO rats as compared to untreated 2VO rats. These results clearly indicate that ibuprofen is an effective neuroprotective agent in chronic cerebral hypoperfusion-induced neurodegeneration in rats and can be fruitfully utilized in the management of Alzheimer’s disease.